A para-halogen-modified copper-based metal-organic framework of terephthalic acid and a preparation method and application thereof
Patent Information
- Application Number
- CN202610795025.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-06-04
AI Technical Summary
然而,对于如何通过强吸电子基团(如卤素)实现反向电子调控,构建适度缺电子的铜活性中心以优化关键中间体吸附强度、促进C-C偶联的研究仍相对有限
[0020] This invention utilizes strong electron-withdrawing halogen atoms (Cl, Br) to regulate the electronic structure of the copper center, breaking through the traditional electron-donating strategy and laying the foundation for highly selective generation of multi-carbon products and hydrocarbons.
Smart Images

Figure CN122325781B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of CO2 reduction catalyst synthesis technology, specifically to a para-halogen modified copper terephthalate-based metal-organic framework material, its preparation method, and its application. Background Technology
[0002] In the electrocatalytic CO2 reduction reaction, the development of cathode catalysts capable of efficiently converting CO2 into multi-carbon products is crucial. Copper-based catalysts have attracted much attention due to their ability to promote CO2 conversion to multi-carbon products, but they suffer from problems such as high overpotential, poor selectivity, and insufficient stability. Metal-organic frameworks (MOFs) have shown great potential in the field of electrocatalysis due to their advantages such as tunable structure, high porosity, and large specific surface area. By designing the metal center and organic ligands of MOFs, their topology and coordination environment can be precisely controlled, thereby achieving selectivity and catalytic activity for specific products. Currently, some studies have aimed to enhance CO2 reduction activity by introducing electron-donating groups such as amino groups to increase the electron density of copper active centers. However, research on how to achieve reverse electron control through strong electron-withdrawing groups (such as halogens) to construct moderately electron-deficient copper active centers to optimize the adsorption strength of key intermediates and promote CC coupling remains relatively limited. In addition, existing copper-based MOF catalysts still have shortcomings in the synergistic design of morphology control and electronic structure. While one-dimensional structures facilitate electron transport and active site exposure, their stability needs improvement; three-dimensional structures offer superior mechanical stability, but their mass transfer efficiency and active site utilization are limited. How to achieve controllable preparation of multi-dimensional catalyst morphologies while introducing halogen electronic modulation, and how to clarify the influence mechanism of halogen type on crystal growth and catalytic performance, remain key scientific problems to be solved in this field. Therefore, developing a halogen-modified copper-based MOF material that combines electronic structure modulation and morphology synergistic optimization is of great significance for improving the selectivity and stability of CO2 reduction to multi-carbon products. Summary of the Invention
[0003] In view of this, the purpose of this invention is to provide a para-halogen modified copper terephthalate-based metal-organic framework material, its preparation method and application, so as to provide a cathode catalytic material for electrocatalytic carbon dioxide reduction reaction, which can achieve efficient electrocatalytic CO2 reduction.
[0004] To achieve the above objectives, this invention provides a method for preparing a copper terephthalate-based metal-organic framework material modified with para-halogens, comprising the following steps:
[0005] 2,5-Dichloro / bromo-terephthalic acid was dissolved in sodium hydroxide solution to deprotonate its carboxyl group, forming a homogeneous precursor solution. Copper nitrate trihydrate solution was slowly added dropwise to the precursor solution under continuous stirring. After sufficient stirring and pre-reaction, the mixed solution was transferred to a reactor for hydrothermal reaction. The reaction product was centrifuged, washed, and dried to obtain a para-halogen-modified copper terephthalate-based metal-organic framework material.
[0006] Preferably, the concentration of the copper nitrate trihydrate solution is 0.05~0.15 mol / L.
[0007] Preferably, the concentration of the 2,5-dichloroterephthalic acid is 0.01~0.03 mol / L.
[0008] Preferably, the concentration of sodium hydroxide is 0.02~0.06 mol / L.
[0009] Preferably, the pre-reaction temperature is room temperature and the stirring time is 20-40 minutes.
[0010] Preferably, the hydrothermal reaction temperature is 80~100℃ and the reaction time is 10~14h.
[0011] Furthermore, the present invention also provides a copper terephthalate-based metal-organic framework material modified with para-halogens, wherein the copper-based metal-organic framework material includes nanorods, three-dimensional nanoflower-like nanorod clusters, and nanobulbs.
[0012] Preferably, the nanorod-shaped copper-based metal-organic framework material has a diameter of 90-150 nm and a length of 2-5 μm; the three-dimensional nanoflower-shaped nanorod cluster copper-based metal-organic framework material is a three-dimensional nanoflower-shaped hierarchical structure formed by the self-assembly of one-dimensional solid nanorods, wherein each nanorod is a solid structure with a length of 2-5 μm and a diameter of 50-100 nm, and the overall cluster aggregate size is 5-10 μm; the nanobulk copper-based metal-organic framework material has a regular and uniform block morphology with a size of 0.5 nm-2 μm.
[0013] Furthermore, the present invention also provides an application of a para-halogen-modified copper terephthalate-based metal-organic framework material as a cathode catalytic material for electrocatalytic carbon dioxide reduction reaction.
[0014] Preferably, the para-halogen-modified copper terephthalate-based metal-organic framework material is dispersed in a solvent, ultrasonically treated to obtain a catalyst slurry, then loaded onto porous carbon paper, and dried to obtain a cathode catalytic material, i.e., a reduction electrode for the electrocatalytic carbon dioxide reduction reaction.
[0015] Preferably, the solvent is ethanol.
[0016] Preferably, the ultrasonic treatment time is 20-60 minutes.
[0017] Preferably, the catalyst loading on the porous carbon paper is 0.3~0.6 mg / cm³. 2 .
[0018] Preferably, the drying temperature is 60-80℃ and the drying time is 3-8 hours.
[0019] The beneficial effects of this invention are:
[0020] This invention utilizes strong electron-withdrawing halogen atoms (Cl, Br) to regulate the electronic structure of the copper center, breaking through the traditional electron-donating strategy and laying the foundation for highly selective generation of multi-carbon products and hydrocarbons.
[0021] This invention successfully solves the problem of strong electron-withdrawing ligands being unable to form regular nanostructures by adjusting the alkaline environment and dynamics of the reaction system, achieving stable coupling between halogen modification and the morphology of one-dimensional high aspect ratio nanorods. The method is relatively mild, highly reproducible, and has the potential for large-scale production.
[0022] This invention provides a synergistic system that combines high specific surface area, axial electron channels, and halogen-modified active sites, simultaneously optimizing mass transfer efficiency, electron conduction, reactivity, and structural stability.
[0023] The material of this invention exhibits excellent hydrocarbon and C content in electrocatalytic CO2 reduction. 2+ Product selectivity, with the highest total Faraday efficiency of up to 62% for hydrocarbons in the products, C 2+ The product achieves a Faraday efficiency of up to 60.7%. This provides a new material system for developing efficient and stable non-precious metal CO2 reduction catalysts.
[0024] This invention, through a comparison of chlorine- and bromine-modified Cu-based MOFs materials, clarifies that the strong electron-withdrawing effect of halogens is crucial for enhancing the performance of Cu-based MOFs. 2+ The study identifies the common key to the selectivity of products and hydrocarbons; and demonstrates that, based on this electronic regulation, the selectivity of specific products can be optimized through morphology design (one-dimensional rods / three-dimensional blocks), thus providing a reliable approach for designing catalysts for different needs. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0026] Figure 1The images shown are FESEM images of the copper terephthalate-based metal-organic framework nanorods modified with para-dichloro and prepared in Example 1 of this invention. In the image, a is a low-magnification FESEM image and b is a high-magnification FESEM image.
[0027] Figure 2 FESEM images of the hierarchical flower-like nanorod clusters of copper terephthalate-based metal-organic frameworks modified with para-dichloro were prepared in Example 2 of this invention, wherein a is a low-magnification FESEM image and b is a high-magnification FESEM image.
[0028] Figure 3 The images shown are FESEM images of the copper terephthalate-based metal-organic framework micro / nano blocks modified with para-dibromo terephthalate prepared in Example 3 of this invention, where a is a low-magnification FESEM image and b is a high-magnification FESEM image.
[0029] Figure 4 The images shown are FESEM images of the halogen-free modified copper terephthalate-based metal-organic framework nanorods prepared in Comparative Example 1 of this invention. In the images, a is a low-magnification FESEM image and b is a high-magnification FESEM image.
[0030] Figure 5 The images shown are FESEM images of copper terephthalate-based metal-organic framework nanorods modified with a single chlorine atom prepared in Comparative Example 2 of this invention. In the images, a is a low-magnification FESEM image and b is a high-magnification FESEM image.
[0031] Figure 6 The images are TEM images of the copper terephthalate-based metal-organic framework nanorods modified with para-dichloro and prepared in Example 1 of this invention. In the images, a is a low-magnification TEM image and b is a high-magnification TEM image.
[0032] Figure 7 The images are TEM images of the hierarchical flower-like nanorod clusters of copper terephthalate-based metal-organic frameworks modified with para-dichloro and prepared in Example 2 of the present invention, where a is a low-magnification TEM image and b is a high-magnification TEM image.
[0033] Figure 8 These are TEM images of the copper terephthalate-based metal-organic framework micro / nano blocks modified with para-dibromo terephthalate prepared in Example 3 of this invention, where a is a low-magnification TEM image and b is a high-magnification TEM image.
[0034] Figure 9XRD diffraction patterns of the copper terephthalate-based metal-organic framework nanorods modified with para-dichloro in Example 1, the hierarchical flower-like nanorod clusters of copper terephthalate-based metal-organic frameworks modified with para-dichloro in Example 2, the copper terephthalate-based metal-organic framework micro / nano blocks modified with para-dibromine in Example 3, the halogen-free modified copper terephthalate-based metal-organic framework nanorods prepared in Comparative Example 1, and the copper terephthalate-based metal-organic framework nanorods modified with a single chlorine atom prepared in Comparative Example 2.
[0035] Figure 10 The Faraday efficiency (Figure a), current performance (Figure b), hydrocarbon selectivity and partial current density (Figure c) of the copper terephthalate-based metal-organic framework nanorods modified with para-dichloro terephthalate prepared in Example 1 of this invention for catalytic CO2 reduction are shown. 2+ Product selectivity and its partial current density (d figure);
[0036] Figure 11 The Faraday efficiency (Figure a), current performance (Figure b), hydrocarbon selectivity and partial current density (Figure c) of the para-dichloro-modified copper terephthalate-based metal-organic framework hierarchical flower-like nanorod clusters prepared in Example 2 of this invention for catalytic CO2 reduction are shown. 2+ Product selectivity and its partial current density (d figure).
[0037] Figure 12 The Faraday efficiency (Figure a), current performance (Figure b), hydrocarbon selectivity and partial current density (Figure c) of the copper terephthalate-based metal-organic framework micro / nanoblocks modified with para-dibromo terephthalate prepared in Example 3 of this invention for catalytic CO2 reduction are shown. 2+ Product selectivity and its partial current density (d figure).
[0038] Figure 13 The Faraday efficiency (Figure a), current performance (Figure b), hydrocarbon selectivity and partial current density (Figure c) of the halogen-free modified copper terephthalate-based metal-organic framework nanorods prepared in Example 1 of this invention for catalytic CO2 reduction are shown. 2+ Product selectivity and its partial current density (d figure).
[0039] Figure 14 The Faraday efficiency (Figure a), current performance (Figure b), hydrocarbon selectivity and partial current density (Figure c) of the copper terephthalate-based metal-organic framework nanorods modified with a single chlorine atom prepared in Example 2 of this invention for catalytic CO2 reduction are shown. 2+ Product selectivity and its partial current density (d figure). Detailed Implementation
[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0041] Example 1: A method for preparing para-dichloro-modified copper terephthalate-based metal-organic framework nanorods, the specific steps of which are as follows:
[0042] (1) Dissolve 241.6 mg of copper nitrate trihydrate in 10 mL of deionized water and sonicate for 10 min to form a copper salt solution;
[0043] (2) Dissolve 80.0 mg of sodium hydroxide in 50 mL of deionized water and sonicate for 5 min to form a sodium hydroxide solution;
[0044] (3) Add 323.9 mg of 2,5-dichloroterephthalic acid to the above sodium hydroxide solution, stir in a water bath at 70°C for 15 min until completely dissolved, and cool to room temperature to obtain a 2,5-dichloroterephthalic acid solution with a concentration of 0.01 mol / L;
[0045] (4) While stirring, add the copper salt solution dropwise to the 2,5-dichloroterephthalic acid solution at a rate of 1 mL / min, and continue stirring for 30 min to obtain the precursor mixture;
[0046] (5) The precursor mixture was transferred into a reactor and hydrothermally reacted at 90°C for 12 hours. After the reaction, the mixture was centrifuged, washed three times with ethanol, and dried at 70°C for 16 hours to obtain blue nanorod-shaped copper-based metal-organic framework powder.
[0047] Example 2: A method for preparing hierarchical flower-like nanorod clusters of copper terephthalate-based metal-organic frameworks modified with para-dichloro, the specific steps of which are as follows:
[0048] (1) Dissolve 241.6 mg of copper nitrate trihydrate in 10 mL of deionized water and sonicate for 10 min to form a copper salt solution;
[0049] (2) Dissolve 80.0 mg of sodium hydroxide in 50 mL of deionized water and sonicate for 5 min to form a clear sodium hydroxide solution;
[0050] (3) Add 323.9 mg of 2,5-dichloroterephthalic acid to the above sodium hydroxide solution, stir in a water bath at 70°C for 15 min until completely dissolved, and cool to room temperature to obtain a 2,5-dichloroterephthalic acid solution with a concentration of 0.01 mol / L;
[0051] (4) While stirring, add the copper salt solution dropwise to the 2,5-dichloroterephthalic acid solution at a rate of 1 mL / min, and continue stirring for 30 min to obtain the precursor mixture;
[0052] (5) The precursor mixture was transferred into a 100 mL reactor and hydrothermally reacted at 70 °C for 12 h. After the reaction, the mixture was centrifuged, washed three times with ethanol, and dried at 70 °C for 16 h to obtain blue nanorod-shaped copper-based metal-organic framework powder.
[0053] Example 3: A method for preparing para-dibromo-modified copper terephthalate-based metal-organic framework micro / nano blocks, the specific steps of which are as follows:
[0054] (1) Dissolve 241.6 mg of copper nitrate trihydrate in 10 mL of deionized water and sonicate for 10 min to form a copper salt solution;
[0055] (2) Dissolve 80.0 mg of sodium hydroxide in 50 mL of deionized water and sonicate for 5 min to form a clear sodium hydroxide solution;
[0056] (3) Add 323.9 mg of 2,5-dibromoterephthalic acid to the above sodium hydroxide solution, stir in a water bath at 70°C for 15 min until completely dissolved, and cool to room temperature to obtain a 2,5-dibromoterephthalic acid solution with a concentration of 0.01 mol / L;
[0057] (4) While stirring, add the copper salt solution dropwise to the 2,5-dichloroterephthalic acid solution at a rate of 1 mL / min, and continue stirring for 30 min to obtain the precursor mixture;
[0058] (5) The precursor mixture was transferred into a 100 mL reactor and hydrothermally reacted at 90 °C for 12 h. After the reaction, the mixture was centrifuged, washed three times with ethanol, and dried at 70 °C for 16 h to obtain blue micro-nano blocky copper-based metal-organic framework powder.
[0059] Example 4: A method for preparing para-dichloro-modified copper terephthalate-based metal-organic framework nanorods, the specific steps of which are as follows:
[0060] (1) Dissolve 120.8 mg of copper nitrate trihydrate in 10 mL of deionized water and sonicate for 10 min to form a copper salt solution;
[0061] (2) Dissolve 40.0 mg of sodium hydroxide in 50 mL of deionized water and sonicate for 5 min to form a sodium hydroxide solution;
[0062] (3) Add 117.5 mg of 2,5-dichloroterephthalic acid to the above sodium hydroxide solution, stir in a water bath at 70°C for 15 min until completely dissolved, and cool to room temperature to obtain a 2,5-dichloroterephthalic acid solution;
[0063] (4) While stirring, add the copper salt solution dropwise to the 2,5-dichloroterephthalic acid solution at a rate of 1 mL / min, and continue stirring for 20 min to obtain the precursor mixture;
[0064] (5) The precursor mixture was transferred into a reactor and hydrothermally reacted at 80°C for 10 h. After the reaction, the mixture was centrifuged, washed three times with ethanol, and dried at 70°C for 16 h to obtain blue nanorod-shaped copper-based metal-organic framework powder.
[0065] Example 5: A method for preparing para-dichloro-modified copper terephthalate-based metal-organic framework nanorods, the specific steps of which are as follows:
[0066] (1) Dissolve 362.4 mg of copper nitrate trihydrate in 10 mL of deionized water and sonicate for 10 min to form a copper salt solution;
[0067] (2) Dissolve 120.0 mg of sodium hydroxide in 50 mL of deionized water and sonicate for 5 min to form a sodium hydroxide solution;
[0068] (3) Add 352.5 mg of 2,5-dichloroterephthalic acid to the above sodium hydroxide solution, stir in a water bath at 70°C for 15 min until completely dissolved, and cool to room temperature to obtain a 2,5-dichloroterephthalic acid solution;
[0069] (4) While stirring, add the copper salt solution dropwise to the 2,5-dichloroterephthalic acid solution at a rate of 1 mL / min, and continue stirring for 40 min to obtain the precursor mixture;
[0070] (5) The precursor mixture was transferred into a reactor and hydrothermally reacted at 100°C for 14 hours. After the reaction, the mixture was centrifuged, washed three times with ethanol, and dried at 70°C for 16 hours to obtain blue nanorod-shaped copper-based metal-organic framework powder.
[0071] Comparative Example 1: The difference from Example 1 is that in step (3), 2,5-dichloroterephthalic acid is replaced with an equimolar amount of terephthalic acid to obtain halogen-free copper terephthalate-based metal-organic framework nanorods; the remaining steps are the same as in Example 1.
[0072] Comparative Example 2: The difference from Example 1 is that in step (3), 2,5-dichloroterephthalic acid is replaced with an equimolar amount of 2-chloroterephthalic acid to obtain copper terephthalate-based metal-organic framework nanorods modified with a single chlorine atom; the remaining steps are the same as in Example 1.
[0073] Performance testing
[0074] The following catalysts were prepared in Comparative Example 1: 15 mg of each of the following nanorod-shaped copper-based metal-organic framework powders: the hierarchical flower-like copper-based metal-organic framework powder prepared in Example 2, the micro / nano-bulb copper-based metal-organic framework powder prepared in Example 3, the halogen-free copper terephthalate nanorods obtained in Comparative Example 1, and the single chlorine atom modified copper terephthalate nanorods obtained in Comparative Example 2. Each nanorod was accurately weighed and dispersed in 15 mL of ethanol solution. 70 μL of D520 perfluorosulfonic acid solution was added, and the mixture was sonicated for 15 min to ensure complete dispersion of the catalyst powder in the mixed solution, thus preparing a uniform catalyst slurry. The catalyst slurry was then uniformly sprayed onto 2 cm × 4 cm carbon paper, with the catalyst loading controlled at 0.5 mg / cm². 2 The catalyst-supported carbon paper was then dried in a vacuum drying oven at 70°C for 2 hours to obtain the cathode of the flow cell. Using the catalyst-supported carbon paper as the cathode, a platinum sheet electrode as the anode, an Ag / AgCl electrode as the reference electrode, a 1.0 mol / L potassium hydroxide solution as the electrolyte, and a fumasep anion exchange membrane as the ion exchange membrane, a three-electrode flow electrolytic cell was assembled. The electrocatalytic performance was tested in the voltage range of -1.8V to -2.8V vs. RHE. The products of the electrocatalytic reduction of carbon dioxide mainly included methane, ethylene, ethanol, and acetic acid.
[0075] Data Analysis:
[0076] like Figure 1 As shown, the material obtained in Example 1 exhibits a uniform one-dimensional nanorod morphology with a length of approximately 2–5 μm and a diameter of approximately 90–150 nm. This one-dimensional nanorod structure with a high aspect ratio has a large specific surface area, which can fully expose copper active sites; at the same time, its continuous axial structure provides an efficient channel for electron transport.
[0077] like Figure 2 As shown, the material obtained in Example 2 exhibits a three-dimensional nanoflower-like hierarchical structure formed by the self-assembly of one-dimensional solid nanorods. Each nanorod is a solid structure, approximately 2–5 μm in length and 50–100 nm in diameter, and they are orderly stacked to form micron-sized aggregates of approximately 5–10 μm in size. This hierarchical structure has a high specific surface area, which is beneficial for the exposure of active sites; simultaneously, the stacking gaps between the nanorods form secondary mass transfer channels, which can promote the diffusion of reactants and products. This structure maintains the overall stability of the material while also possessing a certain mass transfer capacity.
[0078] like Figure 3As shown, the material obtained in Example 3 exhibits a uniform and regular micro / nano block morphology, with its size mainly distributed in the range of 0.5 nm to 2 μm. The difference between this morphology and Cu-based nanorods demonstrates the significant regulatory effect of halogen type on crystal growth. The compactness and regular shape of this micro / nano block structure endow it with good mechanical stability, which is beneficial for constructing a stable and continuous catalytic layer in the electrode; at the same time, its abundant surface provides sufficient active sites, jointly ensuring the high efficiency and stability of the electrocatalytic process.
[0079] like Figure 4 As shown, the material obtained in Comparative Example 1 exhibits a uniformly distributed nanorod morphology.
[0080] like Figure 5 As shown, the material obtained in Comparative Example 2 exhibits a nanorod-like morphology with slightly pointed ends.
[0081] like Figure 10 As shown, when the material obtained in Example 1 was used for electrocatalytic performance testing, the total Faraday efficiency of the nanorod-shaped copper-based metal-organic framework for catalytic conversion of CO2 to hydrocarbons reached a maximum of 62%. 2+ The overall Faraday efficiency of the product reaches a maximum of 60.7%.
[0082] like Figure 11 As shown, when the material obtained in Example 2 was used for electrocatalytic performance testing, the highest total Faraday efficiency of the hierarchical flower-like nanorod cluster copper-based metal-organic framework for catalytic conversion of CO2 to hydrocarbons reached 56.3%. 2+ The overall Faraday efficiency of the product reaches a maximum of 53.2%.
[0083] like Figure 12 As shown, when the material obtained in Example 3 was used for electrocatalytic performance testing, the total Faraday efficiency of the micro / nano bulk copper-based metal-organic framework for catalytic conversion of CO2 to hydrocarbons reached a maximum of 65.5%. 2+ The overall Faraday efficiency of the product reaches a maximum of 53.3%.
[0084] like Figure 13 As shown, when the material obtained in Comparative Example 1 was used for electrocatalytic performance testing, the halogen-free modified nanorod-shaped copper-based metal-organic framework exhibited the highest total Faraday efficiency of 47.3% in the electrocatalytic reduction of CO2 to hydrocarbons. 2+ The overall Faraday efficiency of the product reaches a maximum of 57.5%.
[0085] like Figure 14 As shown, when the material obtained in Comparative Example 2 was used for electrocatalytic performance testing, the overall Faraday efficiency of the nanorod-shaped copper-based metal-organic framework for the electrocatalytic reduction of CO2 to hydrocarbons reached a maximum of 49.69%. 2+ The overall Faraday efficiency of the product reached a maximum of 59.79%.
[0086] In summary, compared with the para-dichloro-modified nanorod-shaped copper-based metal-organic framework (hydrocarbons) in Example 1, the total Faradaic efficiency is up to 62%, C 2+ Compared to the product with a total Faraday efficiency of up to 60.7%, the halogen-free copper-based metal-organic framework nanorods prepared in Comparative Example 1 showed significantly lower selectivity for hydrocarbons during the electrocatalytic CO2 reduction process. 2+ The product selectivity is also slightly lower, and due to Figure 10-13 As shown in the current performance diagram, the total current density and product partial current density of this material at the same potential are significantly lower than those of the para-halogen-modified material; furthermore, compared with the para-dichloro-modified nanorod-shaped copper-based metal-organic framework (hydrocarbons) in Example 1, the total Faradaic efficiency is as high as 62%, C 2+ Compared to the product with a total Faradaic efficiency of up to 60.7%, the total Faradaic efficiency of hydrocarbons obtained by electrocatalytic CO2 reduction from the single chlorine atom-modified copper-based metal-organic framework material prepared in Comparative Example 2 was significantly lower. 2+ The product selectivity was also slightly lower, but compared to the halogen-free copper-based metal-organic framework nanorods in Comparative Example 1, its electrocatalytic reduction of CO2 to hydrocarbons and C2 was significantly better. 2+ The Faraday efficiency of the products increased slightly, and the total current density and the product partial current density increased significantly. This result indicates that a synergistic effect was generated between the para-halogens (two chlorine atoms), and this synergistic effect had a significantly stronger effect on improving catalytic performance than that of single chlorine atom modification.
[0087] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
Claims
1. A method for preparing a para-halogen-modified copper terephthalate-based metal-organic framework material, characterized in that, Includes the following steps: 2,5-Dichloro / bromo-terephthalic acid was dissolved in sodium hydroxide solution to form a homogeneous precursor solution; copper nitrate trihydrate solution was slowly added dropwise to the precursor solution, and after sufficient stirring and pre-reaction, a hydrothermal reaction was carried out to obtain a para-halogen modified copper terephthalate-based metal-organic framework material. The concentration of the copper nitrate trihydrate solution is 0.05~0.15 mol / L; The concentration of the 2,5-dichloro / bromo-terephthalic acid is 0.01~0.03 mol / L; the concentration of the sodium hydroxide is 0.02~0.06 mol / L. The pre-reaction temperature is room temperature, and the stirring time is 20-40 min; The hydrothermal reaction is carried out at a temperature of 80-100℃ for 10-14 hours.
2. A para-halogen-modified copper terephthalate-based metal-organic framework material, characterized in that, The copper-based metal-organic framework material is prepared according to the preparation method described in claim 1; the copper-based metal-organic framework material includes nanorods, three-dimensional nanoflower-like nanorod clusters, and nanobulbs.
3. The para-halogen-modified copper terephthalate-based metal-organic framework material according to claim 2, characterized in that, The nanorod-shaped copper-based metal-organic framework material has a diameter of 90~150nm and a length of 2~5μm.
4. The para-halogen-modified copper terephthalate-based metal-organic framework material according to claim 2, characterized in that, The three-dimensional nanoflower-like nanorod cluster copper-based metal-organic framework material is a three-dimensional nanoflower-like hierarchical structure formed by the self-assembly of one-dimensional solid nanorods. Each individual nanorod is a solid structure with a length of 2~5μm and a diameter of 50~100nm, and the overall cluster aggregate size is 5~10μm.
5. The para-halogen-modified copper terephthalate-based metal-organic framework material according to claim 2, characterized in that, The nano-bulk copper-based metal-organic framework material has a regular and uniform bulk morphology with a size of 0.5 nm to 2 μm.
6. The application of a para-halogen-modified copper terephthalate-based metal-organic framework material according to any one of claims 2-4, characterized in that, It is used as a cathode catalytic material for electrocatalytic carbon dioxide reduction reaction.
Citation Information
Patent Citations
Bi-metal-organic framework structure catalyst and preparing method and application thereof
CN108579815A
A preparing method and application of a three-dimensional nanoflower metal-organic framework material
CN109553779A